On The Generalized Type and Generalized Lower Type of Entire Function in Several Complex Variables With Index Pair (p, q) - Abdali Jaffar, Aiman; Shakir A. Hussein, Mushtaq (Iraqi Journal of Science, 2025)
In the present paper, we will study the generalized ( p, q) -type andgeneralized lower ( p, q) -type of an entire function in several complexvariables with respect to the proximate order with index pair ( p, q) aredefined and their coefficient characterizations are obtained.